2002
DOI: 10.1590/s0103-90162002000200010
|View full text |Cite
|
Sign up to set email alerts
|

External development of the entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae in the subterranean termite Heterotermes tenuis

Abstract: The subterranean termite Heterotermes tenuis is one of the main pests of sugarcane and eucalyptus in Brazil, and the use of entomopathogenic fungi, alone or associated to chemicals, is an efficient and environmentally favorable method for its control. Studies related to the fungal development on these insects are important due to the effect of insect behavior on entomopathogens. The objective of this work was to describe the external development of Beauveria bassiana and Metarhizium anisopliae on H. tenuis usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 16 publications
4
22
0
5
Order By: Relevance
“…So, little but variation in pathogenesis of Beauveria isolates was recorded at different time interval of fungal infection. A similar SEM study showed variation in efficiency and extent of infection among fungal isolates of B. bassiana than M. anisoplae while little variation was recorded in timing and duration of the phases in the infection process for these two isolates (Moino Jr. et al, 2002). Similar to our observations, Gabarty et al (2014) reported adhesion and penetration by B. bassiana and M. anisopliae on Agrotis ipsilon larvae by SEM.…”
Section: Resultssupporting
confidence: 84%
“…So, little but variation in pathogenesis of Beauveria isolates was recorded at different time interval of fungal infection. A similar SEM study showed variation in efficiency and extent of infection among fungal isolates of B. bassiana than M. anisoplae while little variation was recorded in timing and duration of the phases in the infection process for these two isolates (Moino Jr. et al, 2002). Similar to our observations, Gabarty et al (2014) reported adhesion and penetration by B. bassiana and M. anisopliae on Agrotis ipsilon larvae by SEM.…”
Section: Resultssupporting
confidence: 84%
“…The fact that M. anisopliae caused high mortality is suggested to be related to the presence of certain enzymes produced by this fungus (GABRIEL, 1968;ALVES, 1998); another possibility could be the time of infection that occurred faster for M. anisopliae than for B. bassiana s.l. as observed when subterranean termite were exposed (MOINO et al, 2002).…”
Section: Discussionmentioning
confidence: 72%
“…Entre as opções de controle alternativo de carrapato, destaca-se o emprego do controle microbiano que, na área agrícola, já vem sendo utilizado há muito tempo, individualmente ou em programas de manejo integrado de pragas (ALMEIDA, 1994;ALMEIDA et al 1997;BATISTA FILHO et al, 1998;TAMAI et al, 2002;MOINO JUNIOR et al, 2002).…”
Section: Introductionunclassified
“…Levando-se em conta que a coleção do Instituto Biológico conta com grande número de isolados os quais são amplamente utilizados no combate de pragas agrícolas (ALMEIDA et al, 1997;ALMEIDA et al, 1998;MOINO JUNIOR et al, 2002;TAMAI et al, 2002) Para o desenvolvimento do experimento foi utilizada a metodologia descrita por Barci e Nogueira (2006), que permite a observação diária de indivíduos de um mesmo tratamento, pelo menos por 20 dias, sem que haja alteração significativa nos percentuais de mortalidade do grupo controle.…”
Section: Introductionunclassified